College athletes` perceptions of social support and athletic trainer-coach conflict - Newman, N.; Weiss, W. (Journal of Athletic Enhancement, 2017)
Objective: Athletes engage in a cognitive evaluation following an injury to determine if resources are present to manage any potential stress attributed to being injured. This evaluation determines both behavioral and emotional responses to the injury and can be influenced by a number of factors, including social support. Interpersonal conflict could be another factor that influences an injured athlete`s cognitive evaluation. Interpersonal conflict may be present in athletics in the form of athletic trainer-coach conflict. The purpose of this study was to describe the levels of social support and conflict collegiate athletes perceive following an injury, and determine relationships between those perceptions and other variables.